If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 = 3(2p + 3) Reorder the terms: 33 = 3(3 + 2p) 33 = (3 * 3 + 2p * 3) 33 = (9 + 6p) Solving 33 = 9 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 33 + -6p = 9 + 6p + -6p Combine like terms: 6p + -6p = 0 33 + -6p = 9 + 0 33 + -6p = 9 Add '-33' to each side of the equation. 33 + -33 + -6p = 9 + -33 Combine like terms: 33 + -33 = 0 0 + -6p = 9 + -33 -6p = 9 + -33 Combine like terms: 9 + -33 = -24 -6p = -24 Divide each side by '-6'. p = 4 Simplifying p = 4
| .8(x+40)+x=113 | | 6-2(2x-4)=38 | | -3x+7(x+5)=5x-5 | | -5(x+5)+4=-21 | | 6-p=-5 | | 2x+7-2x-4= | | ln(2x)-1=0 | | -0.10(22)+0.45x=0.05(x-12) | | 15+11x= | | 1161=-9(-10x+31) | | 17.75x+24=18.95x+18 | | 6a+2=3a+a | | 4x-3=27+x | | 6y=-8x-1 | | 0.17y+0.07(y+7000)=1690 | | 196x^2+196=200x^2 | | 7d+30=6d+16 | | 2(x-6)-8x=-36 | | 7n^2=252 | | .5a+8.75=13.25+2a | | 8x-24-x+3=0.7 | | 2x-(x+4)=-5-3x+1 | | 9-p=2 | | X-1/9=5/8 | | 3x-5+6x=40 | | -13-(-47)=x/7 | | -5(x-5)+2=27 | | 8.95+1.50=26.95 | | -1.4x=2.67 | | 23/20y=46 | | 0=16x^2-760 | | 6p=-26 |